2015
DOI: 10.1080/13669877.2015.1042507
|View full text |Cite|
|
Sign up to set email alerts
|

Is it all about awareness? The normalization of coastal risk

Abstract: Is it all about awareness? The normalization of coastal riskCoastal risk is already high in several parts of the world and is expected to be amplified by climate change, which makes it necessary to outline effective risk management strategies. Risk managers assume that increasing awareness of coastal risk is the key to public support and endorsement of risk management strategies -an assumption that underlies a common worldview on the public understanding of science, which has been named the deficit model. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 34 publications
1
40
1
4
Order By: Relevance
“…It can be explained as a coping strategy that individuals use to have a sense of control over something that is in fact uncontrollable, and often results in a false sense of security (Johnson and Levin 2009;Luìs et al 2016). This can contribute to increased vulnerability by compromising preparedness efforts.…”
Section: Normalization Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be explained as a coping strategy that individuals use to have a sense of control over something that is in fact uncontrollable, and often results in a false sense of security (Johnson and Levin 2009;Luìs et al 2016). This can contribute to increased vulnerability by compromising preparedness efforts.…”
Section: Normalization Of Riskmentioning
confidence: 99%
“…For example, Renn (1998), Slovic (2001), and Coppola (2011) emphasize the importance of risk awareness and risk perception. Risk awareness can be described as the knowledge and consciousness of the risks associated with a hazard (Raaijmakers et al 2008;Luìs et al 2016). A lack of awareness regarding a risk is likely to result in a lack of preparedness (Scolobig et al 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This is not what would be expected to happen, the less distance to the hazardous source, the more preparedness intention. Literature on psychological processes in risk perception offers some clues to understand these results, particularly on the risk normalisation effect (Luís et al, ). Several studies have shown that psychological proximity does not always lead to more action: some variables such as target behaviour, perceived efficacy or concern, among others, can mediate reducing the effect of psychological distance bias (McDonald, Chai, & Newell, ; Spence et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the classical heuristic processes in taking decisions or making judgements (Tversky & Kahneman, ), mentioned above in point (b), other cognitive bias have recently been adopted to understand RP processes. The study by Luís et al () concludes that normalising perception reduces coastal RP through the illusion of positive control. An example of this conclusion can be found in people living in coastal areas prone to be flooded, who tend to experience a sense of control and an unrealistic optimism about flood hazard.…”
Section: Introductionmentioning
confidence: 99%
“…Such rationalizations of risk exposure have been widely described in risk analytic research (e.g. Luís et al, 2016;Joffe, 2003) as part of individual or collective processes. Breakwell (2001) proposes that these rationalisations become part of social representations and that these representations also contain information about which groups can be trusted or not (Breakwell, 2020), as part of identity defensive strategies.…”
Section: Shifting' Rationalisationsmentioning
confidence: 99%